Nanoapplication of a Resistance Inducer to Reduce Phytophthora Disease in Pineapple (Ananas comosus L.) - Lu, Xinhua; Sun, Dequan; Rookes, James E.; Kong, Lingxue; Zhang, Xiumei; Cahill, David M. (Frontiers in Plant Science, 2019)
Treatment of plants with a variety of abiotic and biotic inducers causes induced resistance to pathogen attack. In this study, the effect of four resistance inducers on plant diseases caused by Phytophthora cinnamomi was screened in vivo initially by using lupin, a susceptible model plant. Lupin pretreated with 0.5 mM salicylic acid (SA) showed effective resistance against P. cinnamomi with restricted lesions. Then, mesoporous silica nanoparticles (MSNs) with particle size around 20 nm and approximate pore size of 3.0 nm were synthesized and functionalized for loading and importing SA to pineapple plantlets. Decanethiol gatekeepers were introduced to the surface of MSNs via glutathione (GSH)-cleavable disulfide linkages to cover the pore entrance, which was confirmed through using Raman spectroscopy. Through free diffusion, the loading efficiency of SA in MSNs gated with gatekeepers was 11.7 %, but was lower in MSNs without gatekeepers (8.0 %). In addition, in vitro release profile of SA from gatekeeper capped MSNs indicated that higher concentrations of GSH resulted in more cargo release. Moreover, the experiments in planta showed that, the application of MSNs as a resistance inducer delivery system significantly improved pineapple resistance to P. cinnamomi in terms of inhibiting lesion development and improving root growth of infected plants, compared to the use of free SA and MSNs without gatekeepers. The analysis of SA, GSH and defense-related genes of PR1 and PR5 further confirmed the slow and prolonged release of SA from MSNs inside the roots of pineapple plants was achieved through a redox-stimuli release mechanism. Therefore, the application of MSNs with redox-responsive gatekeepers has shown great potential as an efficient tool for delivering chemicals into plants in a controllable way.